Twin peaks orchard resort the strategic plan - Cartojano, Marjorie B. (U.P. in Mindanao, 2001)
Valento Farm (not the real business name) is an existing 200-hectare orchard and livestock farm that is presently threatened by the Comprehensive Agrarian Reform Program. The firm is also saddled with low income performance due to low sales volume, and the high interest payments of their huge outstanding loan.